MATEC Web of Conferences - Zakharevich, A. V. specialist in the field of power engineering Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences 1980- (EDP Sciences, 2018)
The results of an experimental investigation of ignition liquid fuel (kerosene, diesel fuel) by the single drops under conditions of radiation-conducting heating in air are presented. The dependences of the ignition delay time of the typical fuels droplets on the initial temperature of the heated oxidant in a limited space are established. The parameters of stable ignition of liquid fuel droplets are set.